Mapping Of Occupation In Quality Management Within National Qualification Framework To Close The Gap Between Education And Industry Needs - Surono, Surono; Anggraini, Ratih Woro (Ridwan Institute, 2024)
In the face of rapid industrial changes and globalization, there is a growing demand for highly skilled professionals in quality management within Indonesia. The Indonesian National Qualifications Framework (IQF) seeks to align vocational education with industry demands by establishing a clear framework of work competency standards. However, discrepancies persist between the competencies taught in vocational programs and those required in the industry, particularly in advanced areas such as data analysis and strategic quality planning. This study undertakes a systematic occupational mapping in the quality management sector to identify these gaps and develop strategies to address them. Utilizing methodologies like the Rapid Assessment Process (RAP), Gall and Borg's educational research methods, and Regional Model Competency Standards (RMCS), the study formulates a comprehensive occupational matrix. This matrix serves as a crucial tool for planning human resources, developing relevant educational and training curricula, and fostering career development aligned with market trends and needs. The research outcomes are aimed at enhancing the alignment of vocational education with industry standards, thereby increasing the employability and effectiveness of graduates in the quality management sector.